Palliative and Hospice Care in Correctional Facilities: Integrating a Family Nursing Approach to Address Relational Barriers. Issue 1 (January 2021) - Burles, Meridith; Holtslander, Lorraine; Peternelj-Taylor, Cindy
Abstract : Background: The need for palliative and hospice care for persons with life-limiting conditions who are incarcerated is increasingly common in correctional facilities worldwide. Objective: Through a family nursing lens, we critically analyze the unique challenges experienced by those requiring palliative care while incarcerated. Key concerns and implications for nursing are illustrated through the discussion of a representative case scenario. Methods: The case scenario was developed based on the findings of a scoping review of academic and gray literature (such as policy documents and editorials) about palliative, hospice, and end-of-life care in corrections. Results: The case scenario highlights multilevel barriers that were identified, including the individual, relational, institutional, and sociocultural contexts of palliative care in correctional facilities. Evidence is presented of how integration of a family nursing perspective can enhance specialized palliative and hospice care services in correctional settings. Conclusions: By applying a family nursing approach, nurses practicing with correctional populations can ensure persons with life-limiting illnesses are not denied their right to appropriate end-of-life care by playing a key role in addressing barriers to palliative and hospice care access in corrections. Specific attention to relational issues and holistic care can contribute to enhanced palliative and hospice care, greater dignity in dying, and improved family and peer outcomes, which have benefits for individuals, families, communities, and society. Implications for Practice: Through the case scenario, we illustrate real issues emerging in correctional contexts and offer evidence of how family nursing relational principles can be applied to promote adequate palliative and hospice care.